Control of base flows using cavities at supersonic Mach number - Nik Hishamuddin, Nik Deanna Asheera; Ali, Mir Sohail; Khan, Ambareen; Khan, Sher Afghan; Pathan, Khizer Ahmed; Chopade, Ramchandra P. (Semarak Ilmu Publishing, 2025)
The occurrence of sudden expansion and flow at the blunt base in the aerospace industry is widespread. Due to flow separation at the base region, a recirculatory region forms, where the pressure is lower than the ambient pressure, resulting in a considerable base drag value. This study investigates the regulation of base flows that are suddenly expanded at a Mach number of 1.6. This study uses internal flow methods to simulate the flow field in the recirculation zone using the passive control technique in the form of a cavity. This paper covers geometrical parameters, including an area ratio of 2.25 and a length-to-diameter ratio of 1:6. Cavities were used as passive controls, and aspect ratios of 3:3 and 6:3 were used to control the base pressure. The location of the cavities was changed from 0.5D to 2D. The inertia parameters considered are the nozzle pressure ratio and the Mach number M = 1.6. The cavity is a passive control method to regulate base pressure and drag. Based on the results, improvements can be made to the aerodynamic design to meet the design specifications. This work also provides the design process for a passive control in terms of the cavity for suddenly expanded flow in a nozzle with a supersonic flow Mach number. The cavity does not adversely influence the flow field in the duct